Molecular Regulation of JC Virus Tropism: Insights into Potential Therapeutic Targets for Progressive Multifocal Leukoencephalopathy - Marshall, Leslie J. (2010)
Progressive multifocal leukoencephalopathy (PML) is a growing concern for patients undergoing immune modulatory therapies for treatment of autoimmune diseases such as multiple sclerosis. Currently, there are no drugs approved for the treatment of PML that have been demonstrated in the patient to effectively and reproducibly alter the course of disease progression. The human polyoma virus JC is the causative agent of PML. JC virus (JCV) dissemination is tightly controlled by regulation of viral gene expression from the promoter by cellular transcription factors expressed in cells permissive for infection. JCV infection likely occurs during childhood, and latent virus containing PML-associated promoter sequences is maintained in lymphoid cells within the bone marrow. Because development of PML is tightly linked to suppression and or modulation of the immune system as in development of hematological malignancies, AIDS, and monoclonal antibody treatments, further scrutiny of the course of JCV infection in immune cells will be essential to our understanding of development of PML and identification of new therapeutic targets.